2010
DOI: 10.1039/b923427f
|View full text |Cite
|
Sign up to set email alerts
|

Direct analysis of melamine in complex matrices using a handheld mass spectrometer

Abstract: A low temperature plasma ambient ionization source, coupled to a portable mass spectrometer (Mini 10.5), is used for the determination of melamine contamination in whole milk and related materials. Thermally assisted desorption and ionization of the analyte was achieved with the plasma probe. The small size, low power consumption and capability for direct sampling without pretreatment makes plasma ionization an appropriate ionization method for use with a handheld mass spectrometer. The standard discontinuous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 42 publications
(56 reference statements)
1
83
0
1
Order By: Relevance
“…Several authors have proposed the direct analysis of MM in milk or pet food using various analytical methodologies. [15][16][17][18][19][20] The LOD for MM in the present study, after considering the 10-fold dilution of the samples, was rather low when compared with those from studies that did not involve prior sample preparation. Rambla-Alegre et al reported a direct injection method for the analysis of MM using HPLC-UV; they obtained an LOD (5 ppb) similar to ours.…”
Section: Analytical Performancementioning
confidence: 75%
See 2 more Smart Citations
“…Several authors have proposed the direct analysis of MM in milk or pet food using various analytical methodologies. [15][16][17][18][19][20] The LOD for MM in the present study, after considering the 10-fold dilution of the samples, was rather low when compared with those from studies that did not involve prior sample preparation. Rambla-Alegre et al reported a direct injection method for the analysis of MM using HPLC-UV; they obtained an LOD (5 ppb) similar to ours.…”
Section: Analytical Performancementioning
confidence: 75%
“…Only a few methods have been proposed for the direct determination of MM in milk or pet foods. [15][16][17][18][19][20] Our proposed method described herein is a facile chromatographic method with membrane microdialysis sampling that allows the simultaneous quantification of MM and CA through direct analysis; it has the advantages that it is cheap and simple to operate and maintain. This developed on-line MD-HPLC system provides good linearity, precision, recovery, and sensitivity over the studied concentration ranges, making it a good choice for analyzing MM and its derivative, CA, in NCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MEL can be desorbed/ionized upon N 2 laser irradiation by simply mixing the commonly adopted MALDI matrixes with melamine cyanurate in urine residue. The high-throughput MEL analysis method using low-temperature plasma (LTP) coupled with an ion trap mass spectrometer of bench top type or handheld mass spectrometer (Huang et al, 2010) have also been introduced recently. The mechanism involves thermally-assisted (from 20 o C to 170 o C) vaporization and plasma ionization of MEL.…”
Section: Screening and Qualitative Methodsmentioning
confidence: 99%
“…A DBD jet operating at a low output power (<5 W) was first applied to desorption/ionization by Harper et al 7 Its suitability for the analysis of drugs, explosives, and food additives [8][9][10][11][12] was demonstrated, but its application to highly sensitive inorganic analysis using ICP-MS has not been studied.…”
Section: Introductionmentioning
confidence: 99%